Population pharmacokinetics and CD20 binding dynamics for mosunetuzumab in relapsed/refractory B‐cell non‐Hodgkin lymphoma - Bender, Brendan; Li, Chi‐Chung; Marchand, Mathilde; Turner, David C.; Li, Feifei; Vadhavkar, Shweta; Wang, Bei; Deng, Rong; Lu, James; Jin, Jin; Li, Chunze; Yin, Shen; et al. (Clinical and translational science, 2024)
Mosunetuzumab (Mosun) is a CD20xCD3 T‐cell engaging bispecific antibody that redirects T cells to eliminate malignant B cells. The approved step‐up dose regimen of 1/2/60/30 mg IV is designed to mitigate cytokine release syndrome (CRS) and maximize efficacy in early cycles. A population pharmacokinetic (popPK) model was developed from 439 patients with relapsed/refractory B‐Cell Non‐Hodgkin lymphoma receiving Mosun IV monotherapy, including fixed dosing (0.05–2.8 mg IV every 3 weeks (q3w)) and Cycle 1 step‐up dosing groups (0.4/1/2.8–1/2/60/30 mg IV q3w). Prior to Mosun treatment, ~50% of patients had residual levels of anti‐CD20 drugs (e.g., rituximab or obinutuzumab) from prior treatment. CD20 receptor binding dynamics and rituximab/obinutuzumab PK were incorporated into the model to calculate the Mosun CD20 receptor occupancy percentage (RO%) over time. A two‐compartment model with time‐dependent clearance (CL) best described the data. The typical patient had an initial CL of 1.08 L/day, transitioning to a steady‐state CL of 0.584 L/day. Statistically relevant covariates on PK parameters included body weight, albumin, sex, tumor burden, and baseline anti‐CD20 drug concentration; no covariate was found to have a clinically relevant impact on exposure at the approved dose. Mosun CD20 RO% was highly variable, attributed to the large variability in residual baseline anti‐CD20 drug concentration (median = 10 μg/mL). The 60 mg loading doses increased Mosun CD20 RO% in Cycle 1, providing efficacious exposures in the presence of the competing anti‐CD20 drugs. PopPK model simulations, investigating Mosun dose delays, informed treatment resumption protocols to ensure CRS mitigation.